2020
DOI: 10.1002/anie.202012209
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Tuned Oxidative [4+2] Annulation and Dioxygenation of Olefins with Hydroxamic Acids

Abstract: This work represents the first [4+2] annulation of hydroxamic acids with olefins for the synthesis of benzo[c][1,2]oxazines scaffold via anode‐selective electrochemical oxidation. This protocol features mild conditions, is oxidant free, shows high regioselectivity and stereoselectivity, broad substrate scope of both alkenes and hydroxamic acids, and is compatible with terpenes, peptides, and steroids. Significantly, the dioxygenation of olefins employing hydroxamic acid is also successfully achieved by switchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 120 publications
0
13
0
1
Order By: Relevance
“…Heterocyclizations are powerful tools for the synthesis of five-membered heterocycles that are often found in natural products , and synthetic pharmaceuticals and widely used in material science and organic synthesis. Recent studies revealed that oxidative heterocyclizations could evoke novel and useful catalytic transformations, which otherwise are difficult to achieve. For example, the cyclization of ketene dithioacetals, a kind of electron-rich olefin, under electrochemical conditions afforded the cyclic amino acid derivatives (Scheme a, X = NH) .…”
mentioning
confidence: 99%
“…Heterocyclizations are powerful tools for the synthesis of five-membered heterocycles that are often found in natural products , and synthetic pharmaceuticals and widely used in material science and organic synthesis. Recent studies revealed that oxidative heterocyclizations could evoke novel and useful catalytic transformations, which otherwise are difficult to achieve. For example, the cyclization of ketene dithioacetals, a kind of electron-rich olefin, under electrochemical conditions afforded the cyclic amino acid derivatives (Scheme a, X = NH) .…”
mentioning
confidence: 99%
“… 3 Despite these landmark achievements, the replacement of the use of an expensive and highly toxic osmium catalyst led to the dioxygenation of alkenes employing other metal-based catalysts which has successfully been developed in the presence of stoichiometric chemical oxidants such as PhI(OAc) 2 or dioxygen (eqn (3) in Scheme 1A ). 4 More recently, transition-metal free approaches such as peroxide 5 or radical-mediated protocols 6 have emerged as the alternative synthetic routes to 1,2-diols, although it is sometimes difficult to predict stereochemical outcome (eqn (4) in Scheme 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in a search for a cost-effective annulation approach, the scientific community has successfully merged transition-metal catalysis with the electrocatalysis . It is a greener oxidant and reductant free approach.…”
mentioning
confidence: 99%